Pengaruh Likuiditas Dan Leverage Terhadap Profitabilitas, Studi Empirik Pada Perusahaan Pembiayaan Yang Listing Di Bursa Efek Indonesia Periode 2010-2014 - Subowo Subowo; Akhmadi Akhmadi (FEB Universitas Sultan Ageng Tirtayasa, 2017)
The purpose of this research to determine the influence of liquidity to profitability. The population of this research is the investment company listed in IDX during 2010-2014 consist of 11 company. Sampling method using purposive sampling. data analyze using multiple regression coefficient which start by assumption test.The result of the influence liquidity (proxy used current ration) not significant to profitability (H1 rejected). The empiric results show that profitability of the company was not defined by the liquidity of the company. While the test to leverage (proxy used debt to equity ratio) was significant to profitability (H2 accepted). This result means leverage has a strategic impact to profitability. Furthermore, the contribute of liquidity and leverage to profitability is about 90,8%.